The Effect of Political and Economic Dimensions on Poverty in Indonesia - Atik Purmiyati; Asan Ali Golam Hassan; Dyah Wulan Sari; Vandi Romadhoni; Nonny Anggela; Laila Rahmadani (Jurnal Ekonomi dan Studi Pembangunan, 2023)
This study aims to identify and analyze the factors that influence poverty of 33 province in Indonesia at 2010-2019. In this study using panel data regression using the Random Effect Model (REM). The independent variables used in this study consisted of the Indonesian Democracy Index (IDI), Economic Institutions, Regional Minimum Wage, Gross Regional Domestic Product (GRDP), Open Unemployment Rate, Mean Years School and Life Expectancy. The results of the study show that simultaneously all independent variables have a significant effect on poverty variables in Indonesia and partially economic institution variables, mean years school, life expectancy, have a negative effect and open unemployment rate variables have a positive effect on poverty in Indonesia in 2010-2019. In addition, IDI, Regional Minimum Wage, GRDP have no significant effect on poverty in Indonesia in 2010-2019.